Isolation, Characterization and Application of Humin From Sumatran Peat Soils as Adsorbent for Naphtol Blue Black and Indigosol Blue Dyes - Maya Rahmayanti; Indah Nurhikmah; Feni Larasati (Universitas Jenderal Soedirman, 2021)
Isolation, characterization and application of humin as adsorbent for naphtol blue black (NBB) and indigosol blue (IB) dyes has been carried out. Humin application in this study aims to obtain the optimum pH conditions and kinetics model for adsorption NBB and IB dyes onto humin. Humin was isolated from peat soils originating from Riau, Sumatra. The isolation method used was the alkaline extraction method and the characterization of humin using FTIR spectrophotometer. The total acidity, carboxylic groups and –OH phenolic groups of humin were determined quantitatively using the acid-base titration method. FTIR characterization indicated the presence of an –OH group which was indicated by the appearance of absorption at a wavelength of 3425.3 cm-1 and a stretching vibration of C=O from the –COOH group at a wavelength of 1705 cm-1. The quantitative calculation of the total acidity value, the content of the carboxylic group and the -OH group phenolics of humin were 508.47 cmol kg-1, 289.42 cmol kg-1 and 219.05 cmol kg-1, respectively. The optimum pH conditions for adsorption NBB and IB onto humin occurred at pH 5 and pH 2, respectively. The adsorption kinetics model of NBB and IB on humin followed the Ho kinetics model.